2013
DOI: 10.1242/jcs.134478
|View full text |Cite
|
Sign up to set email alerts
|

Frs2α and Shp2 signal independently of Gab to mediate FGF signaling in lens development

Abstract: Fibroblast growth factor (FGF) signaling requires a plethora of adaptor proteins to elicit downstream responses, but the functional significances of these docking proteins remain controversial. In this study, we used lens development as a model to investigate Frs2a and its structurally related scaffolding proteins, Gab1 and Gab2, in FGF signaling. We show that genetic ablation of Frs2a alone has a modest effect, but additional deletion of tyrosine phosphatase Shp2 causes a complete arrest of lens vesicle devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 50 publications
3
28
2
Order By: Relevance
“…However, the mechanism by which lens epithelial cells upregulate FGFR expression was previously unclear. Prox1 protein levels are dramatically upregulated in the posterior LV and at the onset of secondary fiber differentiation throughout life (Duncan et al, 2002), a process that is dependent on FGFR signaling in the lens (Li et al, 2014;Zhao et al, 2008). Here, we demonstrate that exogenous FGF is sufficient to stimulate nuclear Prox1 levels in lens explants and that this process requires signaling through the MAPK pathway (see Fig.…”
Section: Prox1 and Fgfrs Form A Novel Regulatory Loop That Regulates supporting
confidence: 51%
“…However, the mechanism by which lens epithelial cells upregulate FGFR expression was previously unclear. Prox1 protein levels are dramatically upregulated in the posterior LV and at the onset of secondary fiber differentiation throughout life (Duncan et al, 2002), a process that is dependent on FGFR signaling in the lens (Li et al, 2014;Zhao et al, 2008). Here, we demonstrate that exogenous FGF is sufficient to stimulate nuclear Prox1 levels in lens explants and that this process requires signaling through the MAPK pathway (see Fig.…”
Section: Prox1 and Fgfrs Form A Novel Regulatory Loop That Regulates supporting
confidence: 51%
“…This raises the interesting question: which intracellular molecules mediate the unique activity of FGF in the lens fiber cells? Recent work suggests that the key transmitters of FGF signaling are Frs2, an adaptor protein specific to FGF tyrosine kinase receptors [206], and Shp2, a protein tyrosine phosphatase [144, 207209]. Constitutively active Ras signaling can compensate for the loss of Frs2 and Shp2 in cell proliferation and differentiation, whereas PI3K signaling rescues an FGF receptor 2 (Fgfr2) deficiency for cell survival, suggesting that FGF signaling employs a compendium of downstream pathways to regulate lens development [146, 207].…”
Section: Reiterative Use Of the Same Genes And Signaling Pathways Dirmentioning
confidence: 99%
“…S1E). We recently showed that FGF signaling requires cooperation between Frs2α and Shp2 to activate Ras signaling in eye development (21,22). This genetic pathway is apparently conserved in skin lesion, as Pten CKO ;Shp2…”
Section: ;Frs2αmentioning
confidence: 99%